Binsyouwi, A Gender Discourse of Biak Women Social Politics Roles in Society: Identity, Hegemonic and Intersectionality - SARI, NOVIETA H (Universitas Diponegoro, 2024)
The focus of this article is the study of Biak women’s discourse, Binsyouwi, a contextualised narrative of Biak women, living a feminist life. Sensational and structural oppressions are discussed with the interlocking ‘walls’ of gender, class and sexism exposed through local and historical narratives and cultural discourse analysis. Binsyouwi is explored to re-articulate agendas for feminist theory and activism in Biak Tribal, particularly their roles in politics, family/household and social life. In the context of a larger discourse on intersectionality, identity, and hegemony anchored in local discourse practices, the study focuses on the 'Mambri Bin' category, portraying her as an extraordinary and knowledgeable woman. It emphasises how important it is to address various forms of oppression to create conscious feminist subjectivities. The study uses intersectionality and gender discourse analysis to investigate the social and political story paradigms of the Binsyouwi figure in Biak society. To clarify the knowledge position of Biak women within their cultural and social setting, it examines feminist theories pertaining to discourse, hegemony, identity, and intersectional praxis in the context of intercultural communication. It also explores the difficulties and systemic power relations. The results show that a variety of factors, including capacity, political stance, economic reasoning, and historical fallacy, influence the levels of stability, rationality, adaptability, and inclusivity. These aspects also appear as common characteristics in the discourse process. In this turn, to improve gender responsiveness in policies and planning, we support cultural communication techniques. This is imperative to address implicit cultural norms around hegemonic masculinity, which call for nuanced and comprehensive communication to reduce bias and promote gender mainstreaming in the development and governance systems.